WATERBORNE PARASITES IN TRINGGUS VILLAGES - Ahmad Syatir, Tahar; Lesley Maurice, Bilung; Kasing, Apun; Yvonne Ai Lian, Lim; Reena Leeba, Richard; Hashimatul Fatma, Hashim; Elexson, Nillian; Lau, Seng (UNIMAS Publisher, 2023)
Waterborne parasites have caused two million mortalities annually particularly among those children below five-year-old children. Accessibility to clean water supply is a fundamental and global issue considering that water contamination by pathogens constitutes high potential to massive outbreaks that can impact economic and social development. Based on the recent statistics by UNICEF, 88% of rural population in Malaysia received basic water supplies from improved sources (i.e. free from outside contamination, principally from faecal matter) in 2015. Within that percentage, there are many rural communities that do not receive piped portable water since they are located remotely from the nearest water treatment facilities. Rural communities which are socially and economically underprivileged such as lack of basic water supplies, can be exposed to various infections sourced from the untreated water.